Reconstituted sorghum grain for finishing swine - G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
Gains of finishing pigs fed whole or rolled reconstituted sorghum grain (30% moisture) from 100 lbs. to an average of 210 lbs. were similar and similar to gains by pigs fed a ground sorghum grain ration. Compared on a 90% dry matter basis, pigs fed the ground ration were 7% more efficient than pigs fed the whole or reconstituted grain rations. Rolling the reconstituted sorghum grain improved feed efficiency (8%) and improved rate of gain as compared to the performance of pigs fed the whole reconstituted grain.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Sorghum grain; Finshing pigs; Rate of gain; Performance